66.3k views
0 votes
What is the solution to

Ax+ bx + C=0

User RollingBoy
by
5.8k points

1 Answer

4 votes

Answer:

x = -C / (A + b)

Explanation:

Without given values for the constants A, b, and C (Assuming they are constants), the best we can do is to isolate the variable x. Let's proceed to solve for x.

Ax + bx + C = 0

x (A + b) + C = 0

x (A + b) = -C

x = -C / (A + b)

So now, when you get the values of the constants A, b, and C, you can plug those in to solve for variable x.

Cheers.

User John Koerner
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.